Providing an Efficient Model for Wireless Sensor Networks Using the Scenario of the Variable Sink Counts Based on the Particle Swarm Algorithm - Akbarirad, M.J.; Ghaemi, R. (Наука та інновації, 2019)
Introduction. A wireless sensor network is a set of independent sensor nodes, which are dispersed in a distributed
manner to monitor and collect data in a geographic environment. One of these problems is the manner of node division in a
set of multi-sink sensors.
Problem Statement. In fact, the main issue in this area is related to the division of sensor nodes between sinks so that
re duced energy consumption and increased network life survival will be resulted. In this study, a solution has been provided
to partition a multi-sink sensor network. Due to the nature of the problem of partitioning a multi-sink sensor network, the
search space is very extensive and, on the other hand, proving that this issue is classified as NP-hard problems has made
the presentation of a definitive solution very difficult.
Purpose. To develop a solution for distribution of sensor network with a few sinks.
Materials and Methods. Thus, given the broad search space of the problem ahead, particle swarm algorithm has been
selected. In order to evaluate the proposed approach, MATLAB programming language has been applied.
Results. The proposed approach has been developed using the criteria of hop counts to the sink and also the number of
cluster heads plus the power of particle search in particle swarm algorithm.
Conclusions. Study of these results in the form of two criteria of hop counts and the number of cluster heads using the
scenario of the variable sink counts demonstrate that in the desired scenario, the proposed approach has been able to
improve hop counts relative to the base method by 17% and the number of cluster heads by 59%. Вступ. Бездротова сенсорна мережа — це набір незалежних сенсорних вузлів, які розподілені певним чином для
моніторингу та збору даних в географічному середовищі. Одним з їхніх функціональних завдань є спосіб розподілу вузлів у наборі датчиків з декількома стоками.
Проблематика. Основна проблема в цій галузі пов’язана з розділенням вузлів датчиків між стоками, що дозволить знизити споживання енергії та збільшити термін служби мережі. У зв’язку з природою проблеми розбиття
сенсорної мережі з декількома стоками, пошуковий простір є надто великим і, з іншого боку, доведення того, що ця
задача є NP-складною проблемою, зробило представлення остаточного рішення дуже складним.
Мета. Розробка рішення розподілу сенсорної мережі з декількома стоками.
Матеріали й методи. З огляду на широкий простір пошуку, в роботі використано алгоритм рою частинок. Для
оцінки запропонованого підходу застосовано мову програмування MATLAB.
Результати. Запропонований підхід було розроблено з використанням критеріїв підрахунку кількості транзитних ділянок до стоку, а також кількості головок кластера сумарно з потужністю пошуку частинок в алгоритмі рою
частинок. Висновки. Вивчення отриманих результатів у вигляді двох критеріїв підрахунку кількості транзитних ділянок
та кількості головок кластера з використанням сценарію змінної кількості стоків свідчить, що запропонований
підхід дозволив поліпшити кількість транзитних ділянок відносно базового методу на 17 %, а кількість головок
кластера — на 59 %. Введение. Беспроводная сенсорная сеть — это набор независимых сенсорных узлов, которые распределены
определенным образом для мониторинга и сбора данных в географической среде. Одной из их функциональных
задач является способ распределения узлов в наборе датчиков с несколькими стоками.
Проблематика. Основная проблема в этой области связана с разделением узлов датчиков между стоками, что
позволит снизить потребление энергии и увеличить срок службы сети. В связи с природой проблемы разбиения
сенсорной сети с несколькими стоками, область поиска является слишком большой и, с другой стороны, доказательства того, что эта задача является NP-сложной проблемой, сделало представление окончательного решения
очень сложным.
Цель. Разработка решения распределения сенсорной сети с несколькими стоками.
Материалы и методы. Учитывая обширную область поиска, в работе использован алгоритм роя частиц. Для
оценки предложенного подхода применены язык программирования MATLAB.
Результаты. Предложенный подход был разработан с использованием критериев подсчета количества транзитных участков к стоку, а также количества головок кластера суммарно с мощностью поиска частиц в алгоритме роя частиц.
Выводы. Изучение полученных результатов в виде двух критериев подсчета количества транзитных участков и
количества головок кластера с использованием сценария переменного количества стоков свидетельствует, что предложенный подход позволил улучшить количество транзитных участков относительно базового метода на 17 %, а количество головок кластера — на 59 %.